A Group Therapy Program for Parentally Bereaved Young Adults With Grief Complications: Rationale, Method and Case Examples. (March 2023) - Larsen, Lene Holm; Guldberg, Anitta; Kring, Villy
Considerable effort has gone into studying bereavement in children, adults and the elderly, but few studies have investigated the effects of bereavement or grief interventions in young adults. Even fewer studies have reported on the effect of interventions for young adults with grief complications. The present study seeks to help fill this gap by describing a Danish treatment program specially developed for young adults with complicated grief reactions. The dual process model of coping with bereavement, psychodynamic theory, and a narrative approach provide the foundation for the treatment. In addition, it utilizes an eclectic use of techniques and a group treatment modality that involves providing individual therapy within a group context. The core elements of the treatment are discussed and then exemplified in two case studies.